The ‘Ogoh-Ogoh’ Youth Festival: A Living Structure of Folklore Transmission in the International Tourist Town of Ubud, Bali - Ni Putu Parmini; Sukarini, Ni Wayan; Indrawati, Ni Luh Ketut Mas; Sala, Giulia; Wasista, I Putu Udiyana (Universitas Udayana, 2025)
This ethnographic study examined the annual festival of ogoh-ogoh (giant sculpture) held by youth in the international tourist town of Ubud, Bali. Using participant observation supplemented by semi-structured interviews with youth organizations, ritual specialists, master craftsmen, and artists, along with documentary analysis of institutional protocols and competition frameworks, the study reveals that the intersemiotic translation from narrative to sculptural form maintains the link with Balinese folklore, transforming it into desirable cultural capital through hermeneutic problem-solving that requires consultation of palm leaf lontar manuscripts and the involvement of elders. Visual–spatial and kinesthetic processing generates mnemonic amplification, producing mythological preservation, while adaptive transmission demonstrates young people's mastery of contemporary technologies and administrative skills, reinforcing traditional knowledge, enabling organizational sovereignty, and maintaining epistemic authority through strategic opacity. These findings redefine cultural sustainability beyond the conservation–innovation dichotomy, revealing the folkloric vitality that emerges through modernity and touristic culture.